Neurobrucellosis with hearing loss and cerebellar involvement / A case report - (:unkn) unknown (My University, 2001)
Bruselloz yaygın tutulumu olan bir hastalıktır. Doğrudan santral sinir sistemi tutulumu nadirdir. Optik, okulomotor, abdusent, fasiyal ve vestibulokoklear sinirler sık tutulan kraniyal sinirlerdir. Bunların içinde sensorinöral işitme kaybına yol açacak şekilde vestibulokoklear sinirin tutulma eğilimi vardır. Burada akut ataksi ve odyometri ile tespit edilen işitme kaybı ile başvuran bir hasta sunulmaktadır.

Brucellosis is a disease of ubiquitous distribution. Direct CNS infection is quite rare.Cranial nerves commonly involved are optic,oculomotor, abducent, facial and vestibulocochlear nerves. Among these there seems to be a predilection for the vestibulocochlear nerve leading to sensorineural hearing loss. We report a patient presenting with acute onset of ataxia and sensorineural hearing loss shown on audiometry.
İşitme kaybı ve serebellar tutulumlu nörobruselloz / Olgu sunumu
Keywords: Genel ve Dahili Tıp